2020
DOI: 10.1084/jem.20191663
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of CAR- and TCR-T cell–based therapy for chronic infections

Abstract: While therapy with T cells engineered with a chimeric antigen receptor (CAR) or a classical T cell receptor (TCR) is revolutionizing cancer treatment, its adoption in infectious diseases has been met with considerable resistance. Can we find its value for the cure of infections?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 15 publications
0
33
0
1
Order By: Relevance
“…In vitro transcribed TCR mRNA redirected T cells express the transferred TCR genes for several days. Although they display less cytotoxic potential when compared to virally transduced T cells in vitro, [64][65][66], they have proven to be safe and effective in a clinical trial involving a chronic HBV patient with extensive HCC metastasis [58]. Administering multiple escalating infusions of mRNA TCR-redirected T cells specific for HBV antigens resulted in reduction of the metastases, which could not be explained entirely by the direct lytic effect of the administered T cells, but rather by their induction of a secondary antitumor response.…”
Section: Gene Transfer Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro transcribed TCR mRNA redirected T cells express the transferred TCR genes for several days. Although they display less cytotoxic potential when compared to virally transduced T cells in vitro, [64][65][66], they have proven to be safe and effective in a clinical trial involving a chronic HBV patient with extensive HCC metastasis [58]. Administering multiple escalating infusions of mRNA TCR-redirected T cells specific for HBV antigens resulted in reduction of the metastases, which could not be explained entirely by the direct lytic effect of the administered T cells, but rather by their induction of a secondary antitumor response.…”
Section: Gene Transfer Methodsmentioning
confidence: 99%
“…In this study, the TCR paired sequences were identified from cells that were also expressing high levels of IFN-γ and IL-2 after co-culture with tandem minigene-transfected or peptide-pulsed autologous patient APCs. The major limitation of this method is the cell number required to perform the assay, which can be an issue when screening T cell populations where the reactive clonotypes are present at low frequency as in chronic viral hepatitis and cancer [64].…”
Section: Single Cell Sequencingmentioning
confidence: 99%
“…To overcome this problem, engineering of CAR-T cells could be done through mRNA electroporation, rather than using viral transduction, to obtain virus-specific T cells that will survive only for a limited time ( Figure 3 ). The use of mRNA electroporation has been shown to result in only transient expression (3–5 days) of the CAR and thus is expected to decrease the risk for its off-target effects [ 81 ]. This technological adaptation can also reduce the viral contamination that can come from the viral transduction method of conventional CAR-T cell engineering.…”
Section: Chimeric Antigen Receptor T-cell (Car-t) Therapymentioning
confidence: 99%
“…A recent study demonstrated that the adoptive transfer of grafted T cells provides a promising novel therapeutic approach wherein the retroviral delivery of T cell chimeric antigen receptors (CARs) can enable primary human T cells to detect HBsAg-positive hepatocytes, release IFN-γ and IL-2, and lyse HBV replicating cells [ 148 ]. Another study found that T cells with a CAR specific for HBV envelope proteins could localize to the liver in mice, reducing HBV replication and only causing transient liver damage [ 149 ]; however, the adoption of this approach to treat infectious diseases has been met with considerable resistance [ 150 ].…”
Section: Adaptive Immune Response Modulationmentioning
confidence: 99%